THE IMPORTANCE OF BLENDER IN TEACHING FINE ARTS - Sulaymanova Sevarakhan Bakhodirjon kizi (Modern American Journals, 2025)
This article explores the growing significance of Blender, a free and open-source 3D creation software, in the context of fine arts education. As digital tools increasingly shape contemporary artistic practices, Blender offers a powerful platform for both creative exploration and technical skill development. The study highlights how Blender facilitates a deeper understanding of form, composition, lighting, and spatial relationships through its diverse features, including sculpting, modeling, texturing, and animation. It also examines how the integration of Blender into fine arts curricula fosters interdisciplinary learning, enhances student engagement, and expands creative possibilities beyond traditional media. By analyzing case studies and classroom applications, the research demonstrates that incorporating Blender not only modernizes fine arts education but also prepares students for emerging career paths in digital arts, game design, virtual reality, and animation. Ultimately, the paper argues that embracing such digital tools is essential for keeping fine arts instruction relevant and future-ready.
Keywords: Blender, fine arts education, digital art, 3D modeling, visual communication, art pedagogy, creative technology, animation, digital tools in education, interdisciplinary learning.